2008
DOI: 10.1111/j.1464-410x.2008.07663.x
|View full text |Cite
|
Sign up to set email alerts
|

How long is too long? The effect of the duration of anaesthesia on the incidence of non‐urological complications after surgery

Abstract: OBJECTIVETo examine the association between the duration of anaesthesia and non‐urological complication (NUC) rates after surgery, as the increasing complexity of minimally invasive and laparoscopic procedures in urology has resulted in longer surgery and anaesthesia, and information on the effect of this on NUC rates is limited.PATIENTS AND METHODSWe identified 2196 patients who had open radical nephrectomy or nephron‐sparing surgery at our institution between 1989 and 2002. Patients were subdivided into grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…We also observed that in our cohort, increasing operative time, female gender, and decreasing BMI were associated with increased major complication risks. Although the association of female gender and decreasing BMI is likely an artificial finding with minimal clinical relevance, our findings support previous observations that increasing time under anesthesia may affect postoperative sequelae [29]. …”
Section: Discussionsupporting
confidence: 88%
“…We also observed that in our cohort, increasing operative time, female gender, and decreasing BMI were associated with increased major complication risks. Although the association of female gender and decreasing BMI is likely an artificial finding with minimal clinical relevance, our findings support previous observations that increasing time under anesthesia may affect postoperative sequelae [29]. …”
Section: Discussionsupporting
confidence: 88%
“…Previous observation found that longer anesthesia was associated with an increase in the incidence of perioperative nonurological complications. 32 For this reason, we further classified the complication into surgical complication and nonsurgical complication. We found that ZS score had more predictive power of surgical complications than RENAL and PADUA.…”
Section: Discussionmentioning
confidence: 99%
“…The association between increased operative time and morbidity has been well documented in general and procedure-specific analyses. [11][12][13][14] Several studies 11,12,14 have found that a longer operation is associated with increased rates of infection, wound disruption, and thrombotic events in patients undergoing free flap surgery. In addition, prolonged anesthesia duration may be particularly important in microvascular surgery because flap viability is intimately related to the degree of intraoperative hemodynamic control.…”
mentioning
confidence: 99%